Examination of Apoptotic Effects of High-Dose Toluene on the Brain Cortex and Cerebellum Tissue During the Acute Phase: an experimental study - Tas, Ufuk; Ayan, Murat; Kuloglu, Tuncay; Suren, Mustafa; Cakil, Duygu; Ozyurt, Birsen; Sarsilmaz, Mustafa (Modestum Ltd, 2012)
The aim of this study is to examine the apoptotic effects of high-dose toluene on rat brain cortex and cerebellum tissues during the acute phase. Fourteen albino Wistar rats (180-200 g) were divided into two equal groups (n : 7). While Group I was used as a control group, Group II was applied to a high dose of toluene (5200 mg / kg / gavage). At the end of a three-hour experimental period brain tissue samples were taken from the killed animals and tissues were fixed in % 10 neutral formalin, then, embedded in paraffin and sectioned (thickness, 5 mu m) to determine the immune reactivity of Bax, sections were stained immunohistochemically with avidin biotin-peroxidase method. At the same time the TUNEL method was used for detection of apoptosis in the brain cortex and cerebellum. As a result of the study, increased Bax immune reactivity was seen in the brain cortex (+++) and cerebellum (++++) of toluene treated rats compared to control. The numbers of TUNEL-positive cells were significantly higher in the cerebellum tissues of animals exposed to toluene than the control. Nevertheless there was not a significantly difference in terms of TUNEL positivity between the brain cortex of control and toluene exposed animals. As a result of this study it was shown that a high-dose of toluene can trigger apoptosis of the brain cortex and cerebellum in a very short period of time.
Yüksek doz tolüenin akut dönemde beyin korteksi ve serebellum dokusu üzerindeki apoptotik etkilerinin i?ncelenmesi; deneysel bir çalışma
Keywords: Toluene; apoptosis; brain cortex and cerebellum; rat